Punca Penceraian Pasangan Dewasa Islam: Perspektif Badan Pelaksana - Rogayah Estar Mohamad; Elmi Baharuddin; Noorazean Razali; Nurul Ashiqin Jaafar; Nur Filzahruz Mohamad Sah (USIM Press, 2024)
Vol. 26 No. 2 (2021): Special Edition